S imenem Lenina zhivem I pobezhdayem! Lenin vsegda s nami! - Viktorov, B (1969)
Portrait of Lenin in the centre, surrounded by Soviet flags and symbols Poster commemorating the centenary of Lenin's birth. Original title: С именем Ленина живем и побеждаем! Ленин всегда с нами! PO-1493